PELATIHAN PEMBELAJARAN DARING INTERAKTIF DALAM UPAYA MEMAKSIMALKAN PROSES PEMBELAJARAN DITENGAH PANDEMI COVID-19 (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
Online learning is a learning activity carried out using an internet connection. By learning online, students are expected to gain the same knowledge as face-to-face learning, but more relaxed because teaching and learning activities are carried out at home. Counseling and mentoring in interesting technology-based teaching aims to improve teacher competence in classroom learning activities for students in a comfortable and fun way. This activity facilitates economics/accounting teachers to be able to improve their professionalism in the management of distance learning. The learning process that integrates technology using several digital media will continue to be used not only in online learning but offline learning. The implementation of the training went well and the participants were enthusiastic in the process of delivering material and practice. The results of the activity evaluation show that teachers have an open mind to online learning, especially the use of virtual (zoom meetings) and Google Classroom which can be accessed anytime and anywhere. Training activities can also support the development of professionalism in online-based learning (online).